Ventral—Dorsal Functional Contribution of the Posterior Cingulate Cortex in Human Spatial Orientation: A Meta-Analysis - Burles, Ford; Umiltá, Alberto; McFarlane, Liam H.; Potocki, Kendra; Iaria, Giuseppe (Frontiers in Human Neuroscience, 2018)
The retrosplenial cortex has long been implicated in human spatial orientation and navigation. However, neural activity peaks labeled ‘retrosplenial cortex’ in human neuroimaging studies investigating spatial orientation often lie significantly outside of the retrosplenial cortex proper. This has led to a large and anatomically heterogenous region being ascribed numerous roles in spatial orientation and navigation. Here, we performed a meta-analysis of fMRI investigations of spatial orientation and navigation and have identified a ventral - dorsal functional specialization within the posterior cingulate for spatial encoding vs spatial recall. Generally, ventral portions of the posterior cingulate cortex were more likely to be activated by spatial encoding, i.e. passive viewing of scenes or active navigation without a demand to respond, perform a spatial computation, or localize onself in the environment. Conversely, dorsal portions of the posterior cingulate cortex were more likely to be activated by cognitive demands to recall spatial information or to produce judgments of distance or direction to non-visible locations or landmarks. The greatly varying resting-state functional connectivity profiles of the ventral (centroids at MNI -22, -60, 6 and 20, -56, 6) and dorsal (centroid at MNI 4, -60, 28) posterior cingulate regions identified in the meta-analysis supported the conclusion that these regions, which would commonly be labeled as ‘retrosplenial cortex’, should be more appropriately referred to as distinct subregions of the posterior cingulate. We suggest that future studies investigating the role of the retrosplenial cortex and posterior cingulate in spatial tasks carefully localize activity in the context of these identifiable subregions